Hidrogéis à base de quitosana/poli (álcool vinílico) para liberação de fármaco visando uso potencial como curativo - Guimarães, Aracelle de Albuquerque Santos (2018)
The aim of this work was to prepare and characterize chitosan (CS) and poly (vinyl alcohol) (PVA) hydrogels, and different CS / PVA compositions, with and without addition of clay (AN) and Ibuprofen (IBU) for a dermal matrix, to be tested as a drug carrier vehicle and used as a wound dressing. They were prepared by the solvent evaporation method and analyzed qualitatively by the visual aspect, them they were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), thermogravimetry (TG ), swelling, contact angle, ultraviolet-visible (UV-Vis) spectroscopy, scanning electron microscopy (SEM), degradation test, and the tensile test. The results of DRX for the hydrogels in the presence of AN and IBU exhibited the formation of nanocomposites with interleaved morphologies ordered for the compositions PVA + AN + IBU, CS/PVA (1:2), (1:3) and (1:4) + AN + IBU and exfoliated morphology for the composition CS/PVA (1:1) + AN + IBU. The contact angle measurements, a dominant hydrophilic character was observed for the composition CS/PVA (1:4) + 1% AN + 10% IBU, both in saline and PBS. Regarding to swelling, an increase in the degree of swelling in water (pH 6.05) was observed for all compositions of hydrogels relative to the compositions analyzed in PBS (pH 7.2). In the drug release assay, it was evidenced that the increase of the PVA content and the incorporation of the clay in the different compositions of CS/PVA hydrogels, played a fundamental role in the modulation of the drug release profile, indicating to be promising in the development of hydrogels to be used as dressings in the treatment of injured tissues, The composition CS/PVA (1:4) + 1% AN + 10% IBU presented the best control in the release profile, and therefore, it was suggested for this purpose. It could also be noted that the hydrogels had tenuous, compatible and suitable properties to be used as curatives, such as burns.